Smart Hydroponics Innovation: Blyink IoT Application for Sustainable Food Security - Fadhilah, Habil Azmi; Purwantini, Lucky; Chairunnisa, Nurlaila Maysaroh; Putra, Purnama; Khoiriyah, Ummi (Entrepreneurship and Community Development, 2024)
The rapid development of technology has a significant impact on various fields, one of which is technology in agriculture. The use of technology in agriculture, such as the Internet of Things (IoT), aims to make it easier for farmers to monitor, manage and carry out agricultural activities. The solution for farmers to utilize technology in monitoring agricultural land to get more effective and efficient harvests so that they can increase productivity and yields is by using IoT technology. The application of IoT technology in hydroponic farming systems can be done to determine the parts per million (ppm) content in water and water levels in real-time. The method used in this community service is socialization and training for farmers in Medalkrisna Village, as well as testing using the prototyping method connected to the Blynk application. This tool allows farmers to monitor parts per million of water and water levels online and makes it easier for farmers to monitor. The managerial implications of implementing Blyink’s Internet of Things-based hydroponic system to improve food security include increasing the efficiency of resource management and optimizing agricultural production.